Should Investment Companies Be Subject to a New Statutory Self-Regulatory Organization? - Joel Seligman (Washington University Law Quarterly, 2005)
When one focuses on investment company accountability, one ultimately can pursue an internal or an external model or some combination of both. Professor Langevoort’s symposium article well describes the more limited role that investment company boards play in contrast to corporate boards and how much more robust market forces such as a market for corporate control are with respect to corporate boards. Indeed, some like Richard Phillips have gone further and suggested that shareholder voting and independent directors on investment company boards should be scrapped altogether. Each investment company could be viewed as a product, with only the mutual fund complex having a board. These type of considerations militate in favor of relying on external accountability mechanisms. As a practical matter, SEC and State Attorney General enforcement actions should be viewed as a residual mechanism. The real issue is how to prevent dysfunction from occurring in the first place. From this perspective a new SRO makes particular sense. It could augment investment company boards, help investment companies themselves receive more rulemaking attention from the SEC, and, most significantly, help avoid the type of scandals that recently have besmirched the reputations of so many mutual fund families. Would it be worth the cost? I suggest now is the time to study seriously that type of empirical question.
Keywords: Institutional investments; Capital market; Securities industry -- Self-regulation; Corporate governance; Industry self regulation; Investment companies; Investment management; Investment Company Act of 1940; United States